Fiscal competition in a transition economy - Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
The paper analyses fiscal competition for mobile capital between identical regions in a transition country.A framework similar to Keen-Marchand (1997) is used to analyse welfare effects of regional competition.It is shown that in very early transition when the share of the old sector is overwhelming, consumers in a transition economy may be better off in a competitive equilibrium.The decision-makers, however, would prefer to coordinate their fiscal policies.
URN:NBN:fi:bof-201408072053
Keywords: 330